Pengaruh Kualitas Produk terhadap Loyalitas Pelanggan pada PO Trijaya - Shevchenko, Ricky; Kosasih, Hengky; Lisa (Journal of Trends Economics and Accounting Research, 2024)
Loyal customers have a relatively permanent, long-term fanaticism towards an item from the company of their choice, do not want to switch to another product, and even influence other parties to use that product. The purpose of this research is to find out whether there is an influence of product quality on customer loyalty at PO Trijaya. The results of the correlation coefficient test show that the coefficient value is 0.727, so it can be said that the product quality variable and the customer loyalty variable have a strong correlation. The results of the coefficient of determination test show that the coefficient of determination value is 0.529, so it can be said that 52.9% of the customer loyalty variable is influenced by the product quality variable, while the remainder is influenced by other variables not mentioned in this research. From the results of hypothesis testing, the Z-count value (7.57) is greater than the Z-table (1.96), so H0 is accepted and Ha is accepted. Thus, service quality has a significant effect on customer loyalty at PO Trijaya